Evaluating Mandibular Condyle Position Changes After Orthognathic Surgery: A Systematic Review and Meta-Analysis - Sharifi, Ali (2025)
Present research aims to evaluate mandibular condyle position changes after bilateral sagittal split osteotomy and bimaxillary orthognathic surgery. Relevant keywords were searched in the international databases Cochrane, Embase, and MEDLINE (PubMed and Ovid) up to January 2025. The Newcastle-Ottawa Scale used to determine the quality of the studies. Mean change of condylar values was used as an effect size with random-effects model and REML methods of 95% confidence intervals (CI). Meta-analysis performed using Stata (as of version 17). The mean change of left condylar position pre- and postoperative values of BSSO was -0.28º (ES -0.28º 95% CI; -1.59º, 1.03º; p<0.05). Non-significant mean values of condylar position pre- and postoperative of BSSO and bimaxillary orthognathic surgery in left sagittal plane was observed (p>0.05). The mandibular condyle position after surgery is influenced to some extent by orthognathic surgery.